Physical fitness and body build parameters of children and adolescents participating in the physical activity promotion programme "Athletics for all!" - Joanna Baj-Korpak; Kamil Zaworski; Marek Wochna; Sebastian Chmara; Marian Jan Stelmach (BMC, 2024)
Abstract Background This study attempts to analyse physical fitness and basic anthropometric parameters of children and adolescents participating in the nationwide physical activity promotion programme "Athletics for All!" (AFA). The programme aims to establish a national system for diagnosing, selecting, recruiting, and identifying talents in youth training. It also aims to build a career development path for athletics, forming the basis of a new structure for youth training in Poland. The primary goal of this study was to assess physical fitness of AFA participants over the years of its implementation (2015-2022) and to identify the leading motor ability with consideration for age, gender, and body build parameters determined with Body Mass Index and Ponderal Index. Methods Nationwide measurements of basic anthropometric parameters as well as physical fitness tests were conducted among 31,790 girls (F) and 22,260 boys (M) participating in the AFA programme. Physical fitness assessments were performed using the OSF test (3 × 10 m shuttle run, standing broad jump, 1 kg medicine ball throw, 4-minute run). Comparative analysis of OSF test results, considering gender, was conducted using the independent samples T-test. The strength and direction of correlations between variables were calculated using the rho-Spearman coefficient. Results OSF test results were converted into points, considering age and gender. Gender was found to be a significantly differentiating factor in physical fitness of AFA participants. Among twelve- and fifteen-year-olds, statistically significant differences were observed in all analysed variables, i.e. in each of the four tests and the overall score. It was noted that the examined girls aged 11 to 17 exhibited higher levels of strength compared to their male counterparts. Statistical analysis revealed significant correlations between OSF test results and the age and body build indicators, with the strength of the correlations being negligible in most cases. Conclusions Participants of the nationwide programme "Athletics for All!" demonstrate a high level of physical fitness, with endurance being a fundamental motor ability. Physical fitness levels show significant correlations with the anthropometric parameters of children and adolescents. The study results confirm the need and justification for implementing physical activity promotion programmes for the younger generation.